2020
DOI: 10.1111/ijlh.13278
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sysmex XN‐10 red blood cell parameters for screening of hereditary red blood cell diseases and iron deficiency anaemia

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Erythrocytic parameters has been already used to help the diagnosis of haemoglobinopathy and membranopathy. Automated reticulocyte indices can differentiate hereditary from acquired spherocytosis ( 4 , 6 ). A previous study, combining reticulocyte count, leukocyte count, and pain in the pelvis and spine, demonstrated a good negative predictive value for ACS risk in SCD ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Erythrocytic parameters has been already used to help the diagnosis of haemoglobinopathy and membranopathy. Automated reticulocyte indices can differentiate hereditary from acquired spherocytosis ( 4 , 6 ). A previous study, combining reticulocyte count, leukocyte count, and pain in the pelvis and spine, demonstrated a good negative predictive value for ACS risk in SCD ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated, with RBC, MCV and MCHC, the possibility of diagnostic orientation in SCD ( 25 ). Nivaggioni et al, demonstrated the interest of combining MicroR, MCHC and IRF to differentiate hereditary RBC diseases as spherocytosis and SCD ( 4 ). In our study, we observed an association of increased reticulocyte count and increased reticulocyte/IRF during crises.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nivaggioni et al analyzed hematological parameters from the Sysmex XN-10 (a different analyzer than the Sysmex XN-1000) using a two-step decision by classification and regression tree (CART) to predict types of anemia, including iron deficiency anemia, heterozygous haemoglobinopathy, sickle cell disease syndrome, hereditary spherocytosis and other, in 8217 patients (15+ years) from a hospital in France [ 15 ]. Here, the CART method found that the percentage of microcytes, RDW, percentage of nucleated red blood cells, MCH, and immature reticulocyte fraction resulted in a correct disorder classification rate of 99.4%.…”
Section: Discussionmentioning
confidence: 99%